Fluorine-free Ti3C2Tx (T = O, OH) nanosheets (∼50–100 nm) for nitrogen fixation under ambient conditions. Issue 24 (5th June 2019) - Li, Tengfei; Yan, Xudong; Huang, Lujun; Li, Jinghan; Yao, Lulu; Zhu, Qianying; Wang, Weiqiang; Abbas, Waseem; Naz, Raheela; Gu, Jiajun; Liu, Qinglei; Zhang, Wang; et al.
Abstract : Due to its fuel-efficient and environmentally friendly nature, the electrocatalytic nitrogen reduction reaction (NRR) has drawn significant attention. Abstract : Due to its fuel-efficient and environmentally friendly nature, the electrocatalytic nitrogen reduction reaction (NRR) has drawn significant attention. However, most of the catalysts reported for the NRR are noble metals or oxides, which are expensive and poorly conductive. Therefore, the development of effective electrocatalysts for nitrogen (N2 ) fixation under ambient conditions has become a promising field. Herein, we report fluorine-free Ti3 C2 T x (T = O, OH) nanosheets with a small size (∼50–100 nm lateral size) as catalysts for the NRR. The as-prepared materials achieved a high NH3 yield (36.9 μg h −1 mgcat −1 ) and faradaic efficiency (9.1%) at −0.3 V vs. reversible hydrogen electrode (RHE) in 0.1 M HCl. The size effect and fluorine-free properties make the performance around two times higher than that in the case of a fluorine-based treatment. This paper inspires us to pursue the extreme size ( e.g. quantum dots) of MXenes which will enhance its NRR property greatly.